Risk Management Practices: A Critical Diagnosis of Some Selected Commercial Banks in Bangladesh - Alam, Md Zahangir; Musukujjaman, Md (Journal of Business and Technology (Dhaka), 2012)
The paper is about risk management practices of commercial banks in Bangladesh based on five commercial banks operating in Bangladesh. The number of respondents was 25, five from each bank. While collecting the requisite data, five points Likert Scale has been used. The objective of the study was to critically examine risk management practices of Bangladeshi banks i.e., types of risk facing a bank, procedure and techniques used to minimize the risk etc. The study also examines how far the banks follow the guidelines of Bangladesh Bank regarding risk management. The study reveals that credit risk, market risk and operational risk are the major risks to the bankers which are managed through three layers of management system. The Board of Directors performs the responsibility of the main risk oversight, the Executive Committee monitors risk and the Audit Committee oversees all the activities of banking operations. In the context of opinions regarding use of risk management techniques, it is found that internal rating system and risk adjusted rate of return on capital are relatively more important techniques used by banks. Key Words: Risk; Risk Management; Risk Management Techniques; Banking. DOI: http://dx.doi.org/10.3329/jbt.v6i1.9992 Journal of Technology (Dhaka) Vol. 6(1), January-June, 2011 15-35